Taras Krokhmalskii’s 60th birthday (Condensed Matter Physics, 2013)
Taras Krokhmalskii, a senior research fellow of the Institute for Condensed Matter Physics of the National Academy of Sciences of Ukraine (ICMP), a renowned specialist in the field of condensed matter physics celebrated his sixtieth birthday on February 6, 2013.
The editorial board of the "Condensed Matter Physics" joins numerous congratulations to him and wish him to stay in good health, implement his creative ideas, gain new achievements in science, and - last but not least - in his own peculiar way to grasp the Nature and tell us the tale.